Prevalência de adoção intra e extrafamiliar em amostras clínica e não-clínica de crianças e adolescentes Prevalence of intrafamilial and extrafamilial adoption in a clinical and non-clinical setting samples of children and adolescents - Fu I Lee (Brazilian Journal of Psychiatry, 2001)
INTRODUÇÃO/OBJETIVOS: Estudos realizados em diferentes países demonstram que a proporção de crianças e adolescentes adotivos atendidos em clínicas psiquiátricas é maior em relação à verificada nas demais clínicas e na população em geral. O objetivo deste estudo é verificar a prevalência de adoção em amostra clínica e não-clínica, identificando possíveis associações entre tipos de adoção (extrafamiliar e intrafamiliar) e procura de serviço psiquiátrico. MÉTODOS: Estudo de corte transversal, envolvendo crianças de seis a 14 anos: amostra clínica (G1) de um serviço de psiquiatria da infância e da adolescência de uma região da cidade de São Paulo (n=551) e amostra não-clínica (G2) de uma escola localizada na mesma região (n=365). RESULTADOS: A proporção de meninos foi significantemente maior no G1 que no G2 (p<0,001). Observou-se maior prevalência de adoção no G1 (7,4%) que no G2 (4,1%; p=0,048). Entre as crianças adotivas, predominaram a adoção extrafamiliar, na amostra clínica (73,2%), e a intrafamiliar, na amostra não-clínica (60,0%; p=0,030). Entre os meninos adotivos (n=32), também predominaram a adoção extrafamiliar no G1 (80,8%) e a intrafamiliar no G2 (66,7%; p=0,038). Entre as meninas adotivas (n=24), não foram constatadas diferenças entre os grupos G1 e G2 quanto à proporção de adoção extrafamiliar e intrafamiliar (p=0,675). CONCLUSÕES: Os dados sugerem que: (1) crianças adotivas são freqüentemente levadas a serviços de saúde mental; (2) a adoção intrafamiliar é a mais comum na população geral, porém são as crianças adotivas extrafamiliares que mais procuram as clínicas psiquiátricas; e (3) meninos em geral e meninos adotivos extrafamiliares são mais freqüentemente levados a serviços de saúde mental que seus pares do sexo feminino. INTRODUCTION/OBJECTIVES: Researchers from different countries have reported a higher percentage of adopted children seen in psychiatric clinics when compared to other clinics and to the general population. The objective of this study was to verify the prevalence of adopted children in two different setting samples, a clinical and non-clinical one, identifying possible associations between the type of adoption (extrafamilial or intrafamilial) and psychiatric assistance. METHODS: A cross-sectional study was carried out involving two groups of children aged six to 14 years: a clinical sample (G1) drawn from psychiatry service for children and adolescents located in a specific region of the city of São Paulo (N=551), and a non-clinical sample (G2) drawn from a school located in the same region (N=365). RESULTS: There was a greater proportion of boys in G1 (70%) than in G2 (45%; p<0.001). It was observed a greater prevalence of adoption in G1 (7.4%) when compared to G2 (4.1%; p=0.048). Among adopted children, extrafamilial adoption predominated in G1 (73.2%), and intrafamilial adoption predominated in G2 (60.0%; p=0.030). Among adopted boys (N=32), there was still a predominance of extrafamilial adoption in G1 (80,8%) and still a predominance of intrafamilial adoption in G2 (66.7%; p=0.038). Among adopted girls (N=24), there was no difference between the two groups regarding the proportion of extrafamilial and intrafamilial adoption (p=0.675). CONCLUSIONS: These data suggest that: (1) adopted children are often taken to mental health clinics; (2) intrafamilial adoption is more common in the general population, but extrafamilial adopted children are the ones for whom psychiatric assistance is sought; and (3) boys as a whole and the extrafamilial adopted one are more often taken to mental health clinics when compared to girls.